ANALYSIS OF NEW MEDIA THROUGH SOCIAL MEDIA NETWORKS AS A MARKETING TOOL IN THE NEW ERA - Clara V. Mariana; Haetami M. R. Fahmi; Reza Padila, Lalu Muhamad (Universitas Islam Negeri Mataram, 2022)
This research adopts a qualitative technique based on discourse analysis. Data is gathered by observation, book study, and document study. Many corporations leverage social media users as a platform to market and publicize their brands. In addition to the positive aspects of social media and Web 2.0, such as the ease of accessing features and the rapid flow of information and sharing content, it also has negative aspects and dangers such as cyberbullying, identity falsification, hacking and cracking, the danger of viruses that harm software, piracy, plagiarism, and leakage and theft of information. The accessibility of sharing content on social media allows communicators to package communications with certain visual symbols to communicate messages to communicants who are social media users in the new media era.